Sediment toxicity assessment of Guanabara Bay, Rio de Janeiro, Brazil. - Maranho, L. A. [UNESP]; Abreu, I.; Santelli, R.; Cordeiro, R. C.; Soares-Gomes, A.; Moreira, L. B.; Morais, R. D.; Abessa, Denis Moledo de Souza [UNESP] (Coastal Education & Research Foundation, 2009)
Guanabara Bay (GB) comprises of estuarine and marine environments of high ecological and socio-economic relevance, together with port, industrial and urban areas. The anthropogenic activities produce environmental impacts, including the aquatic pollution. The sediment quality assessment is important to evaluate the effects of contamination, once sediments are a repository for most of the contaminants. In this Study, the quality of sediments from GB was evaluated, in rainy and dry periods, throughout the employment of acute toxicity tests with the amphipod Tiburonella viscana, and chronic bioassays with embryos of the sea-urchin Lytechinus variegatus. In the dry period, acute toxicity was found in the sediments from stations 1, 2 3 (NW) and 7 (near Guapimirim Environmental Protection Area). The bioassays with liquid phases showed effects, but were strongly influenced by the unionized ammonia levels, which were high in this period. In the rainy period, acute toxicity was found in sediments samples from stations 1, 2, 3, 6, 8, 10, 11, 12 and 15. Chronic toxicity could be clearly detected, as ammonia concentrations tended to be low in the most part of the samples. The results showed that the sediment toxicity is influenced by precipitation rates, which increase the input of contaminants to the Bay, and also allowed subdividing GB in three main zones: northwest (stations 1, 2, 3, 5), northeast (stations 6, 7, 8, 9) and centre-south (stations 10, 11, 12, 13, 14, 15). Results also showed that the quality of GB sediments is poor, and that toxicity tests could determine the combined effects of pollutants.
Keywords: bioassays; sediment; Ecotoxicology; Guanabara Bay